Der europäische Stabilitätsmechanismus ist eine Hydra - Markus C. Kerber (Wirtschaftsdienst, 2013)
Nachdem das Bundesverfassungsgericht im einstweiligen Verfahren mit Urteil vom 12.9.2012 die Ratifikation des ESM-Vertrags unter Einfügung von Kautelen billigte, fand am 11./12.6.2013 die mündliche Verhandlung in der Hauptsache statt. Der folgende Beitrag gibt die wesentlichen Punkte des Eingangs- und Schlussplädoyers des Verfahrensbevollmächtigten der Klägergruppe Europolis wieder. – – After the German Federal Constitutional Court had given its consent to the ratification of the ESM Treaty in an interim proceeding with judgment dated 12 September 2012, subject to several precautionary provisions, the court audience of the main action took place on the 11-12 June 2013. Apart from the acts approving the ESM and the fiscal treaty as well as the regulation (EU) 1176/2011, the German Constitutional Court dealt intensely with the announcement of the ECB Council dated 6 September 2012 to buy bond issues to an unlimited extent from ESM/EFSF-programme states (the so-called OMT programme). The author is the attorney in the procedure 2 BvR 1824/12 of Professor von Stein and others. The article reproduces the essential points of his opening and closing pleadings.
Keywords: E52; E58; E62; 330